High temperature aniso-thermal-mechanical analysis of superplastic forming tools - Deshpande, Aditya A. (2009)
The main objective of the thesis is to establish a methodology to analyse the anisothermo-mechanical behaviour of a representative large industrial Superplastic Forming (SPF) tool made of XN40F material (40% Ni, 20% Cr, Balance Fe) to identify and evaluate different failure mechanisms to improve and predict the tool life. Sequentially coupled thermo-mechanical analyses under realistic loading conditions are developed within a general purpose non-linear Finite Element (FE) code, ABAQUS to predict and analyse the complex temperature-stress-strain cycles of the SPF tool.